SISTEM INFORMASI SIMPAN PINJAM MENGGUNAKAN METODE ACCRUAL BASIS BERBASIS WEB PADA KOPERASI KSPPS BMT AL-HIKMAH SEMESTA WELERI - Indriyani Indriyani; Sukemi Kamto Sudibyo; Edy Siswanto; Ahmad Ashifuddin Aqham; Dendy Kurniawan (LPPM Politeknik Pratama Kendal, 2026)
A cooperative is an economic institution based on mutual cooperation to improve members’ welfare. KSPPS BMT Al-Hikmah Semesta Weleri, engaged in savings and loans, still manages transactions manually using Microsoft Excel, causing delays and data inaccuracies. This study aims to design a web-based savings and loan information system using the accrual basis method and Database Management System (DBMS) to enhance data accuracy and efficiency.The research uses the Research and Development (R&D) method with a qualitative approach. The results show that the system improves operational efficiency, financial report accuracy, and data retrieval.